Chemogenetic Regulation of CX3CR1-Expressing Microglia Using Gi-DREADD Exerts Sex-Dependent Anti-Allodynic Effects in Mouse Models of Neuropathic Pain - Saika, Fumihiro; Matsuzaki, Shinsuke; Kobayashi, Daichi; Ideguchi, Yuya; Nakamura, Tomoe Y.; Kishioka, Shiroh; Kiguchi, Norikazu (Frontiers in Pharmacology, 2020)
Despite growing evidence suggesting that spinal microglia play an important role in the molecular mechanism underlying experimental neuropathic pain (NP) in male rodents, evidence regarding the sex-dependent role of these microglia in NP is insufficient. In this study, we evaluated the effects of microglial regulation on NP using Gi-designer receptors exclusively activated by designer drugs (Gi-DREADD) driven by the microglia-specific Cx3cr1 promoter. For the Cre-dependent expression of human Gi-coupled M4 muscarinic receptors (hM4Di) in CX3C chemokine receptor 1-expressing (CX3CR1+) cells, R26-LSL-hM4Di-DREADD mice were crossed with CX3CR1-Cre mice. Mouse models of NP were generated by partial sciatic nerve ligation (PSL) and treatment with anti-cancer agent paclitaxel (PTX) or oxaliplatin (OXA), and mechanical allodynia was evaluated using the von Frey test. Immunohistochemistry revealed that hM4Di was specifically expressed on Iba1+ microglia, but not on astrocytes or neurons in the spinal dorsal horn of CX3CR1-hM4Di mice. PSL-induced mechanical allodynia was significantly attenuated by systemic (intraperitoneal, i.p.) administration of 10 mg/kg of clozapine N-oxide (CNO), a hM4Di-selective ligand, in male CX3CR1-hM4Di mice. The mechanical threshold in naive CX3CR1-hM4Di mice was not altered by i.p. administration of CNO. Consistently, local (intrathecal, i.t.) administration of CNO (20 nmol) significantly relieved PSL-induced mechanical allodynia in male CX3CR1-hM4Di mice. However, neither i.p. nor i.t. administration of CNO affected PSL-induced mechanical allodynia in female CX3CR1-hM4Di mice. Both i.p. and i.t. administration of CNO relieved PTX-induced mechanical allodynia in male CX3CR1-hM4Di mice, and a limited effect of i.p. CNO was observed in female CX3CR1-hM4Di mice. Unlike PTX-induced allodynia, OXA-induced mechanical allodynia was slightly improved, but not significantly relieved, by i.p. administration of CNO in both male and female CX3CR1-hM4Di mice. These results suggest that spinal microglia can be regulated by Gi-DREADD and support the notion that CX3CR1+ spinal microglia play sex-dependent roles in nerve injury-induced NP; however, their roles may vary among different models of NP.